Five Works - Paz, Octavio, 1914-1998 (New York Arcade Publishing, 2012)
"One of the great thinkers of the twentieth century has some of his finest art, culture and literary criticism collected here for the first time. A Nobel laureate, Octavio Paz s lucid poetry has been translated by such luminaries as Mark Strand, Elizabeth Bishop, and Samuel Beckett, while his work as a diplomat earned him the German Peace Prize late in life. His extraordinary essays, however, have rarely been gathered in one place. In Conjunctions and Disjunctions (2005), he explores the duality of human nature in all its variations in cultures around the world. In Marcel Duchamp (2005), he conveys his awareness of Duchamp as a great cautionary figure in our culture, warning us with jest and quiet scandals of the menacing encroachment of criticism, science and even art (New York Times Book Review). In Alternating Current (2005), Paz, with poetic prose and intellectual vigor, displays his determination to bring the world to Mexico and perhaps even Mexico to the world (New York Times Book Review). On Poets and Others (2005) is a true artist s brilliant criticism on sixteen fellow poets. The Monkey Grammarian (1990) is a dazzling exploration of time and reality, xity and decay, and the origin of language."--Publisher's description.
Keywords: Poetry -- Culture -- Art